Concordia ecclesiae : an inquiry into tension and coherence in Philipp Melanchthon's theology and efforts for ecclesiastical unity, especially in 1527-1530 - Andersen, Ragnar (Arbeiten zur historischen und systematischen Theologie, 2016)
Part 1. Melanchthon's theology and politics of religion 1527-30 -- 1527-28 reform of preaching and administration of the sacraments -- 1528-30 rejecting Anabaptism -- 1529 tension in relation to Reformation movements in Strasbourg and Switzerland -- 1530 indispensable reforms : plan of defence before the Emperor and the Empire -- Summary: ecclesiology and double strategy -- Part 2. The reconciliation project and the confession project at the Diet of Augsburg in 1530 -- Melanchthon changes his approach to the Primate of Germany -- Luther exhorts the clergy at the Diet -- Melanchthon's efforts are determined by the reconciliation project -- Luther draws the reconciliation project under the confession project -- The reconciliation project becomes stranded -- Lutherans rally around the confession project -- Summary: more than peace and concord -- Part 3. Background and preconditions, goals and tactics for Melanchthon's double strategy -- Confession and reconciliation: tension and coherence -- Between Erasmus and Luther -- Epistemological preconditions -- Methodological preconditions -- Theological preconditions -- Church-political principles and practice -- Reconciliation for the sake of the gospel -- Luther and Melanchthon: different expectations, different anthropologies -- Summary: Humanistic efforts for the Gospel -- Part 4. Conclusions and outlook -- Summary and conclusions -- Outlook